Legal Protection of Indonesian Migrant Workers based on The Job Creation Law - osgar sahim matompo (Universitas Muhammadiyah Gresik, 2022)
The state is obliged to guarantee and protect the human rights of its working citizens, both at home and abroad, based on the principles of equal rights, democracy, social justice. Protection of Indonesian migrant workers is all efforts to protect the interests of prospective Indonesian migrant workers and / or Indonesian migrant workers and their families in realizing the guaranteed fulfillment of their rights in all activities. This study uses normative juridical methods, the results of this study explain the form of protection of Indonesian Migrant Workers is carried out in several aspects, namely legal, social, and economic given from before work, during work, until after work. The nature of the provision of legal protection against PMI is a protection against ensuring a sense of security from all forms of violence, both physical and psychological, such as harassment, rape, torture, persecution, murder, expulsion. The protection aims to avoid acts of arbitrariness on the part of people or groups and the state. The job creation law requires Indonesian migrant workers placement companies to have permits that meet business licenses and are issued by the central government, and deposit money to government banks in the form of deposits of at least Rp1.5 billion rupiah that can be disbursed at any time to meet obligations in the protection of Indonesian migrant workers.